Activation of Hsp90 Enzymatic Activity and Conformational Dynamics through Rationally Designed Allosteric Ligands. Issue 39 (18th August 2015) - Sattin, Sara; Tao, Jiahui; Vettoretti, Gerolamo; Moroni, Elisabetta; Pennati, Marzia; Lopergolo, Alessia; Morelli, Laura; Bugatti, Antonella; Zuehlke, Abbey; Moses, Mike; Prince, Thomas; Kijima, Toshiki; et al.
Abstract Hsp90 is a molecular chaperone of pivotal importance for multiple cell pathways. ATP‐regulated internal dynamics are critical for its function and current pharmacological approaches block the chaperone with ATP‐competitive inhibitors. Herein, a general approach to perturb Hsp90 through design of new allosteric ligands aimed at modulating its functional dynamics is proposed. Based on the characterization of a first set of 2‐phenylbenzofurans showing stimulatory effects on Hsp90 ATPase and conformational dynamics, new ligands were developed that activate Hsp90 by targeting an allosteric site, located 65 Å from the active site. Specifically, analysis of protein responses to first‐generation activators was exploited to guide the design of novel derivatives with improved ability to stimulate ATP hydrolysis. The molecules' effects on Hsp90 enzymatic, conformational, co‐chaperone and client‐binding properties were characterized through biochemical, biophysical and cellular approaches. These designed probes act as allosteric activators of the chaperone and affect the viability of cancer cell lines for which proper functioning of Hsp90 is necessary.